PENERAPAN MODEL COOPERATIVE INTEGRATED READING AND COMPOTITION (CIRC) TERHADAP HASIL BELAJAR MATEMATIS SISWA KELAS III SD NEGERI 204 KUAMANG - Dwi Nofri Asmara; Muhammad Subhan; Irpan Sopyan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to apply the cooperative integrated reading and composition (CIRC) model to improve the learning outcomes of class III students at SDN 204 Kuamang in mathematics subjects. Applying this model aims to improve students' mathematical learning outcomes. This type of research is experimental research, in this research a quantitative approach is carried out in the form of a pre-experimental design type one group pretest-posttest design (initial test and single group final test). Before implementing the CIRC model, the teacher first gives pretest questions which aim to compare before and after implementing the model. After being given pretest questions, the CIRC model is applied which aims to improve students' mathematical learning outcomes. After applying the model, they move on to the final phase, namely giving posttest questions which aim to see whether there is an influence before and after implementing the (CIRC) model. After comparing the pretest and posttest scores, it was found that the pretest scores got an overall average score of 47.45, while the posttest scores got an average score of 90.90. So it can be concluded that the implementation of the cooperative integrated reading and composition (CIRC) model was declared successful because students' scores increased significantly after implementing this model.